1971
DOI: 10.1159/000152423
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of Le<sup>a</sup>, A and H Antigens in Salivas of Australian Caucasians and Aborigines

Abstract: Aboriginal secretors synthesize greater concentrations of H, A and Lea antigens than do Caucasians but, in Ax secretors, most H determinants are converted to A. Since Aboriginal secretors have concentrations of Lea in the saliva similar to those of Caucasian non-secretors, it is suggested that the red cell phenotype, Le(a+b+), observed in over 10% of Aborigines, is due to the high concentration of Lea which is not converted to Leb. Aboriginal A1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…This is not dissimilar to information on Aborigines where Boettcher and Kenny [2] showed that this ethnic group synthesised greater concen trations of Lea and H antigens than Euro peans.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…This is not dissimilar to information on Aborigines where Boettcher and Kenny [2] showed that this ethnic group synthesised greater concen trations of Lea and H antigens than Euro peans.…”
Section: Discussionsupporting
confidence: 43%
“…In adults the Lewis Le(a+b+) pheno type has been previously noted in 11.3% of New Zealand Maoris [1], and in over 10% of Australian Aborigines [2], in one white Australian [3], in Japanese [4,5], 1 % of Chilcotin Indians [6], in a Norwegian [7], a black American [8] and also in some Sibe rians [9]. The absence of the Le(a + b +) phe notype has been reported in many other population groups [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is true for other investigations as well [1][2][3][4]6]. The probable explanation for this fact was advanced by Boettcher [1].…”
Section: Discussionmentioning
confidence: 70%
“…The comparable observation in vitro would be that A or B specilicity is not added to Leh structures, which is the conclusion reached on serological grounds by Boettcher and Kenny [3]. Thus, the biochemical evidence indi cates that the H gene acts before Le for, if it did not, the Leh antigen could not be formed.…”
mentioning
confidence: 56%
“…However, since only secretor individuals express the Leh antigen and, at the biochemical level, the Leh antigen is considered to arise where the Lea and I I antigens arc located adjacently on the same oligosaccharide chain, it is apparent that there is interaction, at least at the phenotypic level, between the H and the Lea antigen. Boettcher and Kenny [3] studied H. A and Lea antigens in salivas from australian aborigines, among whom the uncommon red cell phenotype Le(a + b -L) had been found in 13% of the secretors. They found that aborig ines synthesize significantly greater quantities of H and Le11 antigens than Caucasians and.…”
mentioning
confidence: 99%